Valorization of coffee Silverskin into a novel dietary Fiber ingredient: A comprehensive study on structure, and in vitro/in vivo antioxidant activity - Chen Dai; Run Tang; Ziyu Guo; Weixing Yang; Xiaoyu Gao; Jun Sheng; Yang Tian; Jia Liu (Food Research International, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Climatic drying-wetting cycles induced dynamic coupling effect between 3D soil desiccation cracking and moisture redistribution - Yu-Xuan Chen; Jun-Zheng Zhang; Chao-Sheng Tang; Run-Yang Lan; Qing Cheng; Jin-jian Xu; Ben-Gang Tian (Journal of Hydrology, 2026)

A new chlorine-containing flavanol and four new phenylpropanoids from Toddalia asiatica - Bing-Ying Zheng; Zhan-Tao Zhao; Feng Wu; Nan An; Shu-Qi Wu; Lu Gan; Sheng Yin; Run-Zhu Fan; Gui-Hua Tang (Natural Product Research, 2026)

Iridoids from the edible flowers of Rhododendron pachypodum: structural elucidation and healthspan related bioactivities in Caenorhabditis elegans - Ying Wang; Hou-Run Zhang; Jie Luan; Qi Cheng; Bing Chen; Xiang-Qin Tang; Xiao-Mei Yan; Yong-Ming Yan; Jiang-Bo He (Phytochemistry, 2026)

Hirsutanines H−O, monoterpene indole alkaloids from Uncaria hirsuta with neuroprotective effects - Nan An; Lei-Ming Wu; Shu-Qi Wu; Jia-Luo Huang; Dong Huang; Fang-Yu Yuan; Yi-Ling Liao; Run-Zhu Fan; Xian-Yuan Yang; Gui-Hua Tang; Lu Gan; Sheng Yin (Phytochemistry, 2026)

Reconstructing the spatiotemporal distribution of microbial-induced carbonate precipitation using electrical conductivity tomography - Jun-Zheng Zhang; Chao-Sheng Tang; André Revil; Chao Lv; Jin-Jian Xu; Run-Yang Lan; Qi-You Zhou (Engineering Geology, 2026)

RNA interference with the selenoprotein M gene inhibits the growth promoting effect by selenium supplementation to silkworm Bombyx mori - Run-Hui Ma; Wen-Jie Ge; Fei Hu; Ting-Ting Hong; Kiran Thakur; Shun-Ming Tang; Zhao-Jun. Wei (Journal of Asia-Pacific Entomology, 2026)

Whole-genome sequencing reveals the genetic diversity of Aeromonas from freshwater fish and the presence of novel genomic islands carrying clinically important antimicrobial resistance genes - Xiao-Qin Wang; Ke Wu; Run-Min Kang; Heng Lin; Lu-Ya Liu; Ting Xian; Yi-Zhi Tang; Xin Yang; An-Yun Zhang; Hong-Ning Wang; Chang-Wei Lei (Aquaculture, 2026)

Distributed proximal primal–dual splitting for coupled constrained optimization over directed unbalanced networks - Run Tang; Huaqing Li; Dawen Xia; Liang Ran; Jun Li; Wei Zhu (Swarm and Evolutionary Computation, 2026)

Two new compounds from the roots of Mirabilis jalapa L. and their cytotoxic activity in vitro - Xiao-Mei Yan; Tian-Tian Qu; Jie Luan; Hou-Run Zhang; Xiang-Qin Tang; Xiao-Xu Bi; Ying Wang; Bing Chen; Jiang-Bo He (Phytochemistry Letters, 2025)

Status and prediction of soil erosion affected by climate change and human activity in the red-soil region of southern China - Junjie TANG; Xuchao ZHU; Huiyun XU; Dongdong LIU; Shiyu XIE; Wenquan LIU; Run MIAO; Xiaotong DAI (Pedosphere, 2025)

Iridoids and other constituents from the aerial parts of Patrinia rupestris and their inhibitory effects on nitric oxide production - Zhi-Yuan Liu; Sheng-Run Guo; Jian-Xian Tang; Chun-Yan Zhao; Li Pu; Li-Zhong Wang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2025)

Degradation of biodegradable plastic films in soil: microplastics formation and soil microbial community dynamics - Yue Wang; Run-Hao Bai; Qi Liu; Qiu-Xiang Tang; Chang-Hong Xie; Aurore Richel; Christophe Len; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Formation and sensory properties of novel Pyrazinones in the Glycylalanine and Alanylglycine dipeptide Maillard reaction systems - Yue Luo; Run Li; Siyue Zhu; Qingrong Huang; Baojun Xu; Chi-Tang Ho (Food Chemistry, 2025)

A critical review of human internal exposure to short-chain chlorinated paraffins and its concerning health risks - Ke Fang; Yi-bin Sun; Run-ming He; Jian-kun Qian; Wen Gu; Yi-fu Lu; Zhao-min Dong; Yi Wan; Chao Wang; Song Tang (Environmental Research, 2025)

Development of a hybrid algorithm for the simultaneous retrieval of aerosol optical thickness and fine-mode fraction from multispectral satellite observation combining radiative transfer and transfer learning approaches - Chenqian Tang; Chong Shi; Husi Letu; Shuai Yin; Teruyuki Nakajima; Miho Sekiguchi; Jian Xu; Mengjie Zhao; Run Ma; Wenwu Wang (Remote Sensing of Environment, 2025)

Carbon–sulfur–calcium isotopic variability of lower Cambrian shale-hosted carbonate concretions: Insights into growth mechanisms and calcium cycling - Xiqiang Zhou; Xiyuan Chen; Tongxuan Du; Jian Sun; Dongjie Tang; Run Li; Kang-Jun Huang; Yi Ding; Daizhao Chen (Sedimentary Geology, 2024)

High permeability Performance TFC Nanofiltration Membrane with Two dimensional Nanochannels Support Layer Fabricated by Dissolving of Nanosheets - Run-Hua Tang; Shu-Jun Deng; Sheng-Nan Zhao; Yong Shi; Jing Ye; Gui-E Chen; Zhen-Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Validation and revision of low latitudes cloud base height from ERA5 - Dan Li; Yuzhi Liu; Run Luo; Weiqi Tang; Jie Gao; Ziyuan Tan (Atmospheric Research, 2024)

Integrative Metabolomics and Whole Transcriptome Sequencing Reveal Role for TREM2 in Metabolism Homeostasis in Alzheimer’s Disease - Meng Wang; Tao Wei; Chaoji Yu; Ruiyang Li; Yunsi Yin; Hanchen Yang; Run Di; Xinyi Xia; Qi Qin; Yi Tang (Molecular Neurobiology, 2024)

Stratigraphic evidence for a major unconformity within the Ediacaran System - Run Li; Xiqiang Zhou; Michael P. Eddy; Ryan B. Ickert; Zhenfei Wang; Dongjie Tang; Kang-Jun Huang; Peng Peng (Earth and Planetary Science Letters, 2024)

The simultaneous removal of methylene blue (MB) and Ca2+ by recyclable adsorbents based the scales derived from coal gasification system - Bai-Hong An; Da-Mao Xu; Run-Ting Wang; Ye-Xuan Wen; Rui Geng; Jia-Yun Wu; Xian-Chun Tang; Hong-Bin Chen (Environmental Science and Pollution Research, 2024)

Long-term exposure to reduced specific-size ambient particulate matter and progression of arterial stiffness among Chinese adults - Dankang Li; Shouling Wu; Linxi Tang; Shuohua Chen; Feipeng Cui; Yudiyang Ma; Run Liu; Jianing Wang; Yaohua Tian (Journal of Hazardous Materials, 2024)

Residential greenness and incident idiopathic pulmonary fibrosis: A prospective study - Linxi Tang; Feipeng Cui; Yudiyang Ma; Dankang Li; Jianing Wang; Run Liu; Yaohua Tian (Environmental Research, 2024)

Evaluation and uncertainty analysis of Himawari-8 hourly aerosol product version 3.1 and its influence on surface solar radiation before and during the COVID-19 outbreak - Chenqian Tang; Chong Shi; Husi Letu; Run Ma; Mayumi Yoshida; Maki Kikuchi; Jian Xu; Nan Li; Mengjie Zhao; Liangfu Chen; Guangyu Shi (Science of The Total Environment, 2023)

Continuous Co-incorporation of Chinese Milk Vetch and Rice Straw with Reduced Chemical Fertilizer Maintains Rice Yield as a Consequence of Increased Carbon and Nitrogen Storage in Soil Aggregates - Rongyan Bu; Wenlong Cheng; Shang Han; Run Hu; Hui Wang; Shan Tang; Min Li; Qin Zhu; Ji Wu; Weidong Cao (Journal of Soil Science and Plant Nutrition, 2023)

Bed level changes in the surf zone during post-storm beach recovery - Pengpeng Hu; Zhiqiang Li; Chunhua Zeng; Daoheng Zhu; Run Liu; Qianxin Su; Jieping Tang; Yamin Zhu (Frontiers in Marine Science, 2023)
The study of post-storm beach recovery is important for economic development and the protection of life in coastal areas. In this study, field observations were conducted for 21 days in the surf zone of Dongdao Beach, Hailing Island, China, after tropical storm “Cempaka”. Data on depth, wave, Eulerian velocity, sediment, three-dimensional topography of the beach, and high-frequency variations in bed-level elevation were collected. The results showed that the beach experienced medium- to low- to medium-energy waves during field observations and covered two complete astronomical tide cycles. Contrary to the effect of wave energy conditions on beaches under normal wave conditions, a higher wave energy during beach recovery can promote silting and accelerate beach recovery. Tidal water level is an important factor affecting beach restoration, and a smaller tidal range is conducive to beach accretion. In a mixed semidiurnal tide, beach erosion and accretion occurred in the “highest tide” and “sub-highest tide” tidal cycles, respectively, and the combined effect of the two affected the change in the bed level in a mixed semidiurnal tide. After the storm, the hydrodynamic forcing mechanism and self-organization process of the sand bar jointly drove the formation of the topography of the bar channel in the surf zone. After the storm stopped, the spectral energy in free surface elevation was mainly distributed in the very low frequency and decayed rapidly at the infragravity band. The very low-frequency pulsation of the surf zone during recovery is a prominent feature of bed-level elevation, depth, and velocity. This study provides a good case for the study of hydrodynamic and bed level changes in the post-storm surf zone, as well as a reference for future studies of the intrinsic mechanisms post-storm beach recovery processes around the world.

Examining the impacts of implicit economic policy on urban environmental pollution: Unveiling pathways for sustainable recovery - Ya Yang; Mengru Zhou; Yawei Hou; Run Tang; Bo Liu; Yue Deng (Resources Policy, 2023)

Resource curse, economic efficiency and green recovery based on three-subject framework - Shiya Gao; Xin Guan; Run Tang; Junfan Zhu; Zeyu Wang; Wei Xu (Resources Policy, 2023)

Failure mechanism of a large-scale composite deposits caused by the water level increases - Xin Zhang; Guo-xiang Tu; Qi-feng Luo; Hao Tang; Yu-lin Zhang; An-run Li (Journal of Mountain Science, 2023)

Diversity of sesquiterpenoids from Stellera chamaejasme with neuroprotective effects - Fang-Yu Yuan; Zhuo-Ya Tang; Xue-Long Yan; Dong Huang; Han-Zhuang Weng; Jia-Luo Huang; Run-Zhu Fan; Ye Chen; Sheng Yin; Gui-Hua Tang (Phytochemistry, 2023)

How much urban air quality is affected by local emissions: A unique case study from a megacity in the Pearl River Delta, China - Meng-Xue Tang; Xiao-Feng Huang; Pei-Ting Yao; Run-Hua Wang; Zhi-Jie Li; Chao-Xi Liang; Xing Peng; Li-Ming Cao; Ke Du; Kuangyou Yu; Song Guo (Atmospheric Environment, 2023)

Forest hydrology modeling tools for watershed management: A review - Ge Sun; Xiaohua Wei; Lu Hao; María González Sanchis; Yiping Hou; Rasoul Yousefpour; Run Tang; Zhiqiang Zhang (Forest Ecology and Management, 2023)

Screening and production of dsRNA molecules for protecting Cucumis sativus against Cucumber mosaic virus through foliar application - Qin Mo; Beibei Lv; Yu Sun; Xiao Wu; Lili Song; Run Cai; Xueming Tang (Plant Biotechnology Reports, 2022)

Euphanoids A and B, two new lathyrane diterpenoids with nitric oxide (NO) inhibitory activity from Euphorbia kansuensis - Xue-Long Yan; Run-Zhu Fan; Jun Sang; Xing-Lin Xie; Gui-Hua Tang; Sheng Yin (Natural Product Research, 2021)

Effects of aerosols on cloud and precipitation in East‐Asian drylands - Run Luo; Yuzhi Liu; Qingzhe Zhu; Yuhan Tang; Tianbin Shao (International Journal of Climatology, 2021)
Extensive observational and numerical simulations have been performed to better characterize the role of aerosols in affecting the clouds and precipitation. However, due to the large uncertainties of aerosol property, the effect of aerosols on clouds and precipitation over the arid and semiarid region (briefly called ‘drylands’) of East Asia (EA) is still unclear. Basing on observations and model simulations from the Coupled Model Intercomparison Project Phase 5 (CMIP5), we investigated the aerosol's effects on the cloud properties and precipitation over the drylands of EA from 1850 to the present and projected forward to 2,300. It is found that, during 1850–2005, with the mean aerosol optical depth (AOD) over the drylands of EA increasing, the cloud droplet number concentration (CDNC) increases, while the cloud effective droplet radius (CEDR) decreases significantly at a rate of −0.40 μm·century −1 . Besides, the cloud water path (CWP) and precipitation show slightly increasing trends with the AOD increasing. Additionally, the effect of aerosols on cloud properties is saturated when the AODs reach 0.21 and 0.15 over the arid region (AR) and semiarid region (SR), respectively. According to the prediction for the period 2006–2300, the AOD and CDNC tend to decline over the drylands of EA, while the CWP, CEDR and precipitation show increasing trends. Particularly, the aerosol, clouds and precipitation indicate more significant changes over the SR in EA during 2006–2300. In future research, there is an urgent need to quantify the contribution of aerosol‐cloud interaction to the precipitation change over the drylands of EA.

Genome-Wide Identification and Expression Analysis of Heavy Metal Stress–Responsive Metallothionein Family Genes in Nicotiana tabacum - Qin Yu; Linshen He; Chunsong Huo; Xiaohan Jiang; Hua Chen; Run Wang; Minzhi Tang; Ling Dong; Ji Chen; Yonghao Li; Shunqin Zhu; Wanhong Liu (Plant Molecular Biology Reporter, 2021)

Effect of the number of coplanar rock bridges on the shear strength and stability of slopes with the same discontinuity persistence - Peng Tang; Guo-Qing Chen; Run-Qiu Huang; Dong Wang (Bulletin of Engineering Geology and the Environment, 2021)

Prediction and Identification of Epitopes in the Emy162 Antigen of Echinococcus multilocularis - Ming-Quan Pang; Feng Tang; Hai-Jiu Wang; Ying Zhou; Li Ren; Run-Le Li; Hu Zhou; Chen-Fei Wan; Chuan-Chuan Liu; Cai-Rang Yangdan; Hai-Ning Fan (Acta Parasitologica, 2020)

Brittle failure of rockslides linked to the rock bridge length effect - Peng Tang; Guo-Qing Chen; Run-Qiu Huang; Jing Zhu (Landslides, 2020)

Structural Changes, Volatile Compounds and Antioxidant Activities of Maillard Reaction Products Derived from Scallop ( Patinopecten yessoensis ) Female Gonad Hydrolysates - Jia-Run Han; Yi-Nan Du; Yue Tang; Jun Zhao; Wen-Hui Shang; Jia-Nan Yan; Hai-Tao Wu; Bei-Wei Zhu (Journal of Aquatic Food Product Technology, 2019)

The jasmonate-responsive transcription factor CbWRKY24 regulates terpenoid biosynthetic genes to promote saponin biosynthesis in Conyza blinii H. Lév. - Wen-Jun Sun; Jun-Yi Zhan; Tian-Run Zheng; Rong Sun; Tao Wang; Zi-Zhong Tang; Tong-Liang Bu; Cheng-Lei Li; Qi Wu; Hui Chen (Journal of Genetics, 2018)

Rheological Behavior of Protein Hydrolysates from Papain-treated Male Gonad of Scallop ( Patinopecten yessoensis ) - Jia-Run Han; Jia-Nan Yan; Yi Li; Jun Zhao; Yue Tang; Wen-Gang Jin; Wen-Hui Shang; Meng Zhang; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2018)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Phytochemicals and biological activities of Artemisia sieversiana - Shi-Jun Liu; Zhi-Xin Liao; Zhi-Shu Tang; Chun-Li Cui; Hong-Bo Liu; Yan-Ni Liang; Yu Zhang; Huan-Xian Shi; Yao-Run Liu (Phytochemistry Reviews, 2017)

Silencing of HMGA2 promotes apoptosis and inhibits migration and invasion of prostate cancer cells - Zhan Shi; Ding Wu; Run Tang; Xiang Li; Renfu Chen; Song Xue; Chengjing Zhang; Xiaoqing Sun (Journal of Biosciences, 2016)

Effect of contact state on the shear behavior of artificial rock joint - Zhi Cheng Tang; Run Qiu Huang; Quan Sheng Liu; Louis Ngai Yuen Wong (Bulletin of Engineering Geology and the Environment, 2016)

Rapid susceptibility mapping of co-seismic landslides triggered by the 2013 Lushan Earthquake using the regression model developed for the 2008 Wenchuan Earthquake - Wei-le Li; Run-qiu Huang; Qiang Xu; Chuan Tang (Journal of Mountain Science, 2013)

Co-seismic landslide inventory and susceptibility mapping in the 2008 Wenchuan earthquake disaster area, China - Wei-le Li; Run-qiu Huang; Chuan Tang; Qiang Xu; Cees van Westen (Journal of Mountain Science, 2013)

Effect of the CYP2C19*2 and *3 genotypes, ABCB1 C3435T and PON1 Q192R alleles on the pharmacodynamics and adverse clinical events of clopidogrel in Chinese people after percutaneous coronary intervention - Xiao-Fang Tang; Jing Wang; Jia-Hui Zhang; Xian-Min Meng; Bo Xu; Shu-Bin Qiao; Yong-Jian Wu; Jue Chen; Yuan Wu; Ji-Lin Chen; Run-Lin Gao; Jin-Qing Yuan; et al. (European Journal of Clinical Pharmacology, 2013)

Eight polymorphic microsatellite loci for the Chinese medicinal plant Artemisia annua L. (Asteraceae) - Hui-Run Huang; Guang Zhou; Xue-Jun Ge; Xiao Wei; Yun-Sheng Jiang; Hui Tang (Conservation Genetics, 2009)

Two new flavanone glycosides from Veratrum nigrum L. - Hui-Liang Li; Jian Tang; Run-Hui Liu; Chuan Zhang; Wei-Dong Zhang (Natural Product Research, 2009)